2000
DOI: 10.1097/00005392-200001000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence, Progression and Success in Stage Ta Grade 3 Bladder Tumors Treated With Low Dose Bacillus Calmette-Guerin Instillations

Abstract: Our study demonstrates the high progression potential of stage Ta grade 3 tumors, since nearly 50% recurred and 25% progressed to invasive disease. These results may be closely compared with the results of previous trials of stage T1 grade 3 disease. We suggest that recurrence should be detected at an early stage using long-term followup with strict observance of the surveillance protocols during a minimum 5-year tumor-free period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 28 publications
1
15
0
1
Order By: Relevance
“…14 In an effort to reduce the potential for complications, some reports have demonstrated sufficient efficacy using a lower dose of BCG. [1][2][3][4][5][6][7][8][9] In these previous studies, the dosedependent response of BCG instillation has not been clearly shown, but lower incidence of adverse effects has been clearly demonstrated.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…14 In an effort to reduce the potential for complications, some reports have demonstrated sufficient efficacy using a lower dose of BCG. [1][2][3][4][5][6][7][8][9] In these previous studies, the dosedependent response of BCG instillation has not been clearly shown, but lower incidence of adverse effects has been clearly demonstrated.…”
Section: Discussionmentioning
confidence: 93%
“…Numerous investigations have been conducted regarding the doses and duration of BCG instillation for improving efficacy and reducing adverse effects. [1][2][3][4][5][6][7][8][9] Several commercially available BCG strains have been adopted for this treatment and it has been reported that the suitable dose of each strain might be different. [10][11][12] The therapeutic efficacy of BCG is related in part to the titer, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Zlotta et al examined HSP60 expression during the humoral response stimulated by BCG in the treatment of patients with superficial bladder carcinoma. Intravesical BCG therapy is accepted as the treatment of choice for patients with noninvasive bladder tumors who have a high risk of recurrence 28–30. BCG therapy uses the Mycobacterium bovis , which contains a very immunogenic protein: HSP60 (65 kD).…”
Section: Discussionmentioning
confidence: 99%
“…The finding of urothelial carcinoma by urine cytology has the greatest implications after TUR or during BCG treatment, but one study found an association between pre-treatment cytology and BCG response, as well as progression [60]. In this way, it might be a surrogate marker for overall high-risk disease, including CIS.…”
Section: Groups At Risk Of Failure (Lowest Level Of Evidence)mentioning
confidence: 99%